A Case of Leser-Trélat Syndrome Associated with a Renal Cell Carcinoma - Dietrich Barth; Silvio Puhlmann; Joachim Barth (Karger Publishers, 2015)
Seborrheic keratoses can often be found in elderly people. In general, they appear gradually. In cases of a sudden eruption with itching it might be paraneoplastic. Although some authors doubt the existence of the paraneoplastic Leser-Trélat syndrome, we present a case of sudden eruption of seborrheic keratoses connected with a newly diagnosed renal cell carcinoma. As far as we know, this is the first case report of a Leser-Trélat syndrome with a malignancy of the kidney.